(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to study and analyze the reality of the internal control system in the company surveyed . To find out how effective and efficient internal control system , problem – centered research that addressed the performance of the internal control system . The research Description applied and the interview Alchksahvi analysis and interpretation of results . The researchers recommended the need for attention to the training courses and the need for segregation of duties and functions in the main and subsidiary records , taking in to account periodic reconciliations between the lists and financial records .